Transfer mechanism of cell-free synthesized membrane proteins into mammalian cells - Umbach, Simon; Levin, Roman; Neumann, Sebastian; Steinmetzer, Torsten; Dötsch, Volker; Bernhard, Frank (Frontiers in Bioengineering and Biotechnology, 2022)
Nanodiscs are emerging to serve as transfer vector for the insertion of recombinant membrane proteins into membranes of living cells. In combination with cell-free expression technologies, this novel process opens new perspectives to analyze effects of even problematic targets such as toxic, hard to express or artificially modified membrane proteins in complex cellular environments of different cell lines. Furthermore, transferred cells must not be genetically engineered and primary cell lines or cancer cells could be implemented as well. We have systematically analyzed basic parameters of the nanotransfer approach and compared the transfer efficiencies from nanodiscs with that from Salipro particles. The transfer of five membrane proteins was analyzed: The prokaryotic proton pump proteorhodopsin, the human class A family G-protein coupled receptors for endothelin type B, prostacyclin and free fatty acids type 2 as well as of the orphan GPRC5B receptor as a class C family member. The membrane proteins were cell-free synthesized with a detergent-free strategy by their cotranslational insertion into preformed nanoparticles containing defined lipid environments. The purified membrane protein/nanoparticles were then incubated with mammalian cells. We demonstrate that nanodiscs disassemble and only lipids and membrane proteins, but not the scaffold protein, are transferred into cell membranes. The process is detectable within minutes, independent from the nanoparticle lipid composition, and the transfer efficiency directly correlates with the membrane protein concentration in the transfer mixture and with the incubation time. Transferred membrane proteins insert in both orientations, N-terminus in and N-terminus out, in the cell membrane and the ratio can be modulated by engineering. The viability of cells is not notably affected by the transfer procedure and transferred membrane proteins stay detectable in the cell membrane for up to three days. Transferred G-protein coupled receptors retained their functionality in the cell environment as shown by ligand binding, induction of internalization and specific protein interactions. In comparison to transfection, the cellular membrane protein concentration is better controllable and more uniformly distributed within the analyzed cell population. A further notable difference to transfection is the accumulation of transferred membrane proteins in clusters, presumably determined by microdomain structures in the cell membranes.